God who speaks with/out words: the philosophical problem of revelation in contemporary Muslim theology - Mirdamadi, Yaser (The University of Edinburgh, 2019)
This thesis explores the philosophical problem of divine revelation in contemporary Muslim theology by focusing critically on the works of ‘Abdolkarim Soroush (b. 1945) an Iranian philosopher, modern theologian, and public intellectual. In a nutshell, the philosophical problem of divine revelation, as specifically related to Islam, centres around making sense of the paradox of the transcendent God who has supposedly spoken like human beings, mainly through the Qur’an. While God is, by definition, the meta-historical Being, the Qur’an is taken to be a book that at least partially reacts to historical events, and therefore not a meta-historical entity. To solve this problem, Soroush argues that the Qur’an, in both content and form, is literally a Muhammadan speech, and only figurately divine speech. Soroush also argues that the Qur’anic speech of Muhammad is, phenomenologically, dreamlike in nature. In this thesis I argue that Muslim theories of revelation can be divided into internalist and externalist theories. While internalist theories recognize, at least in principle, the agency of the prophet in the process of revelation, the externalists refrain from doing so. The Soroushian theory of the Qur’anic revelation is one of the most radical internalist theories of revelation in which the full agency in the process of revelation is given to Muhammad. I also argue in this thesis that the Soroushian theory of the Qur’anic revelation seems to be positioned in the middle between realism and irrealism. For realists, God, as independent being, can be known and talked about cognitively (i.e. in a way that is capable of being true or false). For irrealists, which come in various forms however, either independent God does not exist (ontological anti-realism), or God’s existence or non-existence cannot be known (epistemological anti-realism), or talk of God is not cognitive (non-realism). I argue that while Soroush claims that his theory of religion is realistic, it seems more like a hybrid position between realism and irrealism which at the end laps into irrealism or ends up being not far from it. Specifically, his theory of the Qur’anic revelation seems irrealistic. His theory of religion at the end, then, seems inconsistent: it claims to be realistic but seemingly it is not finally so.
Keywords: Qur’anic concept of revelation; ‘Abdolkarim Soroush; Muhmmad as prophet